KEDUDUKAN WALI DALAM PERNIKAHAN MENURUT IBNU RUSYD - Hasibuan, Pendi (IAIN Bukittinggi, 2009)
Ibnu Rusyd is a popular philosopher and very expert in Islamic law study. In his Islamic book under the title of Bidayah alMujtahid he wrote the arguments of some scholars, and then he analyzes the arguments critically and argues the reason of different arguments appearance. Start from this point, he begins to express his arguments related with the problem discussed. This article will explain about his arguments related the state of guardian in a marriage.